Development of a Cell-Based High-Throughput Screening Assay to Identify Porcine Host Defense Peptide-Inducing Compounds - Zhuo Deng; Jing Wang; Wentao Lyu; Xuwen Wieneke; Robert Matts; Xi Ma; Guolong Zhang (Journal of Immunology Research)
Novel alternatives to antibiotics are needed for the swine industry, given increasing restrictions on subtherapeutic use of antibiotics. Augmenting the synthesis of endogenous host defense peptides (HDPs) has emerged as a promising antibiotic-alternative approach to disease control and prevention. To facilitate the identification of HDP inducers for swine use, we developed a stable luciferase reporter cell line, IPEC-J2/PBD3-luc, through permanent integration of a luciferase reporter gene driven by a 1.1 kb porcine β-defensin 3 (PBD3) gene promoter in porcine IPEC-J2 intestinal epithelial cells. Such a stable reporter cell line was employed in a high-throughput screening of 148 epigenetic compounds and 584 natural products, resulting in the identification of 41 unique hits with a minimum strictly standardized mean difference (SSMD) value of 3.0. Among them, 13 compounds were further confirmed to give at least a 5-fold increase in the luciferase activity in the stable reporter cell line, with 12 being histone deacetylase (HDAC) inhibitors. Eight compounds were subsequently observed to be comparable to sodium butyrate in inducing PBD3 mRNA expression in parental IPEC-J2 cells in the low micromolar range. Six HDAC inhibitors including suberoylanilide hydroxamine (SAHA), HC toxin, apicidin, panobinostat, SB939, and LAQ824 were additionally found to be highly effective HDP inducers in a porcine 3D4/31 macrophage cell line. Besides PBD3, other HDP genes such as PBD2 and cathelicidins (PG1–5) were concentration-dependently induced by those compounds in both IPEC-J2 and 3D4/31 cells. Furthermore, the antibacterial activities of 3D4/31 cells were augmented following 24 h exposure to HDAC inhibitors. In conclusion, a cell-based high-throughput screening assay was developed for the discovery of porcine HDP inducers, and newly identified HDP-inducing compounds may have potential to be developed as alternatives to antibiotics for applications in swine and possibly other animal species.